Analisis Strategi Integrated Marketing Communication Dalam Upaya Meningkatkan Volume Penjualan UMKM Gauri Shop Di Jakarta Timur - Putra, Roland Anggara; Prihadini, Diana (JAMBIS : Jurnal Administrasi Bisnis, 2025)
This studi aims This study aims to determine and analyze the use of Integrated Marketing Communication (IMC) strategies, as well as identify inhibiting factors and efforts to increase sales volume of Gauri Shop MSMEs in East Jakarta. The research method used a qualitative descriptive approach, with data collection techniques including interviews, observation, and documentation. Eight informants were selected using purposive sampling. The research results show that Gauri Shop's implementation of IMC strategies is still suboptimal, particularly in terms of digital media utilization and direct customer interaction. Inhibiting factors identified include limited human resources, capital, and fluctuating purchasing power. Efforts made to overcome these obstacles include strengthening human resource competencies, diversifying promotional content, and improving customer shopping experiences through digital media and physical stores. This research is expected to provide theoretical and practical contributions to the development of integrated marketing strategies for MSMEs in Indonesia to be able to increase competitiveness and sales volume in a sustainable manner